2006
DOI: 10.1038/ni1315
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T cell development by the deubiquitinating enzyme CYLD

Abstract: T cell receptor signaling is essential for the generation and maturation of T lymphocyte precursors. Here we identify the deubiquitinating enzyme CYLD as a positive regulator of proximal T cell receptor signaling in thymocytes. CYLD physically interacted with active Lck and promoted recruitment of active Lck to its substrate, Zap70. CYLD also removed both Lys 48- and Lys 63-linked polyubiquitin chains from Lck. Because of a cell-autonomous defect in T cell development, CYLD-deficient mice had substantially few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
238
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(250 citation statements)
references
References 48 publications
6
238
2
3
Order By: Relevance
“…Loss of CYLD in cylindromatosis is associated with tumor development of hair follicles and sweat and scent glands, which is coincident with increased NF-kB signaling. CYLD has recently been shown to also be important for T-cell development and has been implicated to promote deubiquitination of the T-cell-specific tyrosine kinase Lck (Reiley et al, 2006). NF-kB-induced cell death has also been linked to increased expression of the pro-death factors B7-H1 (PCD ligand 1, pdcd1), which induces apoptosis of T lymphocytes (Dong et al, 2002;Yu et al, 2004;Lee et al, 2005), and caspase-11, which can activate the death effector caspase-3 (Kang et al, 2000;Schauvliege et al, 2002).…”
Section: Mechanisms Implicated In Nf-kb's Proapoptotic Activitymentioning
confidence: 99%
“…Loss of CYLD in cylindromatosis is associated with tumor development of hair follicles and sweat and scent glands, which is coincident with increased NF-kB signaling. CYLD has recently been shown to also be important for T-cell development and has been implicated to promote deubiquitination of the T-cell-specific tyrosine kinase Lck (Reiley et al, 2006). NF-kB-induced cell death has also been linked to increased expression of the pro-death factors B7-H1 (PCD ligand 1, pdcd1), which induces apoptosis of T lymphocytes (Dong et al, 2002;Yu et al, 2004;Lee et al, 2005), and caspase-11, which can activate the death effector caspase-3 (Kang et al, 2000;Schauvliege et al, 2002).…”
Section: Mechanisms Implicated In Nf-kb's Proapoptotic Activitymentioning
confidence: 99%
“…Therefore, the loss-of-function of CYLD may lead to persistent activation of NF-kB to promote the survival of cancer cells (Brummelkamp et al, 2003;Kovalenko et al, 2003;Trompouki et al, 2003). Three groups have recently reported the phenotypes of CYLD knockout mice, which surprisingly are not identical (Massoumi et al, 2006;Reiley et al, 2006;Zhang et al, 2006). Massoumi et al (2006) showed that CYLD-deficient mice are prone to chemical-induced skin cancer, owing, in part, to enhanced K63-polyubiquitination of BCL3, an IkB-like protein that functions as a transcriptional coactivator by forming a complex with the p50 or p52 subunit of NF-kB.…”
Section: Deubiquitination Enzymes Inhibit Tak1 and Ikkmentioning
confidence: 99%
“…In this sense, it has been shown that CYLD-deficiency specifically affects the normal differentiation of T-cells at the level of DP to SP transition. 26 Despite we have demonstrated that reverting CYLD is sufficient to prevent T-ALL in mice, our previous screening shows that both A20 and CYLD are downregulated in T-ALL human samples. 15 These results indicate that A20 and CYLD might compensate each other in some situations or pathologies and require additional mechanisms to be inactivated.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%